Reliability of Three Disability Scales for Detection of Independence Loss in Parkinson’s Disease - Anders Bjornestad; Ole-Bjorn Tysnes; Jan Petter Larsen; Guido Alves (Parkinson's Disease)
Background. Loss of independence is considered an important outcome measure in Parkinson’s disease (PD), but tools to assess dependency have not been tested in PD. Methods. In this study of 158 PD patients, we examined the two most widely used scales and cut-offs for dependency evaluation in PD, the Hoehn and Yahr (HY) stage > 3 and the Schwab and England (SE) scale score < 80%, against a standardized clinical interview assessing dependency in activities of daily living (ADL). We also examined the performance of the generic Barthel ADL index. In addition, we determined whether alternative cut-offs improved the utility of these tools. Results. Compared to clinical interview as gold standard, HY stage > 3 had 21% sensitivity and 98% specificity in detecting dependency in ADL. Corresponding figures for SE score < 80% were 55% and 92%, respectively. Using alternative cut-off values improved the overall diagnostic accuracy only slightly. Barthel ADL index had 67% sensitivity and 78% specificity in detecting dependency at its optimal cut-off value. Conclusion. Both the disease-specific HY staging and SE scale and the generic Barthel ADL index are suboptimal tools for assessing independence loss in PD. Clinical interview should be the assessment of choice in studies of dependency.